prove : (tanθ + sinθ + 1)(tanθ - secθ + 1) /tanθ = 2

Maybe, it's sec in place of sin.
You get to prove it if there was sec in place of sin
you are probably right jackie.. so assume that there is sec theta in the numerator in place of sine theta. and answer it
The questioner says it was given in cbse examination
im so sry ... i consulted my teacher n i came 2 knw that the ques is wrng..!!..sry 4 makin u trouble..


  • Brainly User
It is sec instead of sin. Now consider the numerator it can be written as [(tanA+1)+(secA)][(tanA+1)-(secA)] = (1+tanA)²-(secA)²=1+tan²A+2tanA-1-tan²A=2tanA. Hence you have 2tanA/tanA=2.
you should write clearly each expression on a different line..